Cenário epidemiológico do tracoma no estado do Ceará - Maciel, Adjoane Maurício Silva (2023)
Trachoma, a chronic and recurrent keratoconjunctivitis caused by Chlamydia trachomatis, remains the leading cause of infectious blindness worldwide. It is one of the most povertyrelated NTDs. Objective: To analyse the epidemiological scenario of trachoma in the state of Ceará, Brazil, from 2000 to 2022. Method: An epidemiological study based on mixed designs: Scientometric analysis to study the research profile of trachoma in Brazil from 2000 to 2020; ecological characterisation of demographic, clinical-epidemiological and spatio-temporal distribution patterns based on school and household surveys recorded in the National Information System for Notifiable Diseases (SINAN) in the state of Ceará from 2007 to 2021, and trachoma-related morbidity and mortality data in Brazil from 2000 to 2021, using hospitalisation records from the Hospital Information System (SIH-SUS) and death certificates from the Mortality Information System (SIM); and a cross-sectional analytical survey to estimate the current prevalence of follicular trachoma in children aged 1-9 years and trachomatous trichiasis “unknown to the health system” in adults aged ≥15 years in municipalities with epidemiological and social risk in the Lower Jaguaribe micro-region, State of Ceará, from 2021 to 2022. The study was approved by the Research Ethics Committee of the São José Hospital for Infectious Diseases, Fortaleza, under protocol number 4,060,828. Results: The scientometric analysis identified 42 bibliographic productions and an average of two articles per year nationally, from 55 institutions in seven countries, revealing the limited number of studies on trachoma in the country. In the state of Ceará, the overall average disease positivity rate was less than 5.0% (2.8%, 56,612/2,048,038). However, in the recent past, the health regions of Litoral Leste/Jaguaribe (2012, 2014) and Sertão Central (2012) showed positivity rates ≥10.0%, in addition to municipalities without survey development (44% - 81/184), indicating prevalence levels below the threshold for elimination of the disease as a public health problem. Nevertheless, there were areas with high positivity and limited coverage of surveillance and control measures. A total of 131/49,922,361 hospitalisations (average rate of 0.031/106 population) and 116/26,052,564 deaths (average rate of 0.027/106 population) related to trachoma were identified in Brazil from 2000 to 2021. No cases of follicular trachoma in children aged 1-9 years and trachomatous trichiasis “unknown to the health system” in adults aged ≥15 years were detected in the population-based prevalence survey in the Lower Jaguaribe microregion. Conclusions: Despite the reduction in surveillance and control activities in endemic areas, trachoma is still in the process of elimination. The neglected nature of the disease is compounded by limited research and registration in areas of greater social vulnerability, which calls for increased funding for strategic research to improve management and planning. There is a clear challenge to the sustainability of these interventions, given the possibility of trachoma resurgence in high-risk and vulnerable areas in the state of Ceará. The evaluation and monitoring of data in the information systems is necessary to ensure the completeness and consistency of hospitalisation and death records. These perspectives are of great importance in light of the 2030 target proposed by the WHO to eliminate trachoma as a public health problem, in line with the Sustainable Development Goals (SDGs).